Synthesis of new hemiasterlin derivatives with α,β-unsaturated carbonyl-thiophene groups in fragment A - Chinh, Pham The; Tham, Pham Thi; Tuyen, Nguyen Van (Vietnam Journal of Chemistry, 2017)
Hemiasterlin, an antimitotic tripeptide, exhibits cytotoxicity in the nanomolar range against a variety of cultured human and murine cell lines. For this reason, the synthesis of new hemiasterlin derivatives has attracted a lot of interest in the organic chemistry community recently. In this article, we synthesized new simplified derivatives of hemiasterlin in which the α,α-dimethylbenzylic group in fragment A is replaced by α,β-unsaturated carbonyl-thiophene group. These new compounds will be prepared by classical peptide coupling approach between the carboxylic acid fragments A 12 and dipeptide 13. We expect that this derivative will possess interesting biological activities due to the high reactivity of the α,β-unsaturated carbonyl group as Michael receptor with biological nucleophiles, such as DNA, RN5A, and enzymes. Keywords.Synthesis, hemiasterlin, α,β-unsaturated; tripeptides, nanomolar.